2016
DOI: 10.1121/1.4948574
|View full text |Cite
|
Sign up to set email alerts
|

In-air hearing of a diving duck: A comparison of psychoacoustic and auditory brainstem response thresholds

Abstract: Auditory sensitivity was measured in a species of diving duck that is not often kept in captivity, the lesser scaup. Behavioral (psychoacoustics) and electrophysiological [the auditory brainstem response (ABR)] methods were used to measure in-air auditory sensitivity, and the resulting audiograms were compared. Both approaches yielded audiograms with similar U-shapes and regions of greatest sensitivity (2000À3000 Hz). However, ABR thresholds were higher than psychoacoustic thresholds at all frequencies. This d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…5), and (2) wide-field imaging could potentially capture lower auditory thresholds at hearing onset based on responses in higher auditory nuclei than the levels previously considered in the field. In fact, decades of psychoacoustic experiments on humans and animals indicate that behavioral thresholds can be~20-30 dB lower than those measured with the ABR [49][50][51][52] . Therefore, it is possible that central auditory circuits can pick up signals from just a few peripheral neurons through a cascade of amplification and generate activity detectable with calcium imaging while remaining elusive to the ABR.…”
Section: Discussionmentioning
confidence: 99%
“…5), and (2) wide-field imaging could potentially capture lower auditory thresholds at hearing onset based on responses in higher auditory nuclei than the levels previously considered in the field. In fact, decades of psychoacoustic experiments on humans and animals indicate that behavioral thresholds can be~20-30 dB lower than those measured with the ABR [49][50][51][52] . Therefore, it is possible that central auditory circuits can pick up signals from just a few peripheral neurons through a cascade of amplification and generate activity detectable with calcium imaging while remaining elusive to the ABR.…”
Section: Discussionmentioning
confidence: 99%
“…The ABR test is a relatively stable, objective hearing examination method that reflects the presence of hearing compensatory function by determining the auditory enhancement (Crowell et al, 2016), as it is not affected by the state of consciousness (awake, comatose, sleeping or anesthetized), making it especially appropriate for anesthetized subjects. To our knowledge, research including this method has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results did demonstrate that, (1) central auditory responses in the IC can be detected by calcium imaging while only ABR waves I-II were consistently visible at P14.0 ( Figure 5B and 5D), and (2) wide-field imaging could potentially capture lower auditory thresholds at hearing onset based on responses in higher auditory nuclei than the levels previously considered in the field. In fact, decades of psychoacoustic experiments on humans and animals indicate that behavioral thresholds can be ~20-30dB lowers than those measured with the ABR (Ehret, 1977, R.Fay, 1988, Pinto and Matas, 2007, Crowell et al, 2016. Therefore, it is possible that central auditory circuits can pick up signals from just a few peripheral neurons through a cascade of amplification and generate activity detectable with calcium imaging, while remaining elusive to the ABR.…”
Section: Reduced Auditory Sensitivity In the α9/α10 Nachr Knockout Atmentioning
confidence: 99%